Treatment of Patellofemoral Chondral Lesions Using Microfractures Associated with a Chitosan Scaffold: Mid-Term Clinical and Radiological Results. (December 2021) - Calvo, Rafael; Figueroa, David; Figueroa, Francisco; Bravo, Jose; Contreras, Martin; Zilleruelo, Nicolas
Objective: To assess the clinical and radiological results of patellofemoral osteochondral lesions treated with microfractures associated with a chitosan scaffold. Design: A retrospective observational analytical study was performed. Fifteen patients with full-thickness patellofemoral osteochondral lesions were included. Quantity and quality of the reparation cartilage was assessed with the MOCART 2.0 score on a postoperative magnetic resonance imaging (MRI), and clinical outcomes were evaluated with pre- and postoperative Kujala score tests. Shapiro-Wilk test for normality was applied as well as Wilcoxon's signed rank test and Kruskal-Wallis H test for clinical scores within subjects and patella versus trochlea subgroups comparisons. Analysis of variance test was used for imaging subgroups comparison, with P < 0.05 defined as statistical significance. Results: Mean follow-up was 33.36 months (range 24-60 months). Postoperative Kujala scores improved an average of 19 points compared with the preoperative state (SE = 17.6; P < 0.001). No statistical difference was found through the clinical location assessment ( P = 0.756), as well as the cartilage imaging assessment ( P = 0.756). The mean MOCART 2.0 scale was 67.67 (range 50-85). Conclusions: Treating full-thickness patellofemoral osteochondral lesions with microfractures associated with a chitosan scaffold proved to be effective regarding defect filling and symptomatic improvement.